Household refrigerators: Forced air ventilation in the compressor and its positive environmental impact - Clito F. Afonso (2013)
One of the critical areas in the outer shell of household refrigerators is the compressor compartment, which has relatively high temperatures, due to the heat generated while the compressor is running. This implies a larger heat transfer to the interior air volume and, consequently, more energy consumption. One way to decrease this temperature is to ventilate the base of the refrigerator with a small fan. In the research carried out, a decrease of 11 degrees C in the temperature of the surfaces close to the compressor was recorded, when the fan was running. The implications of this effect can be seen at two levels: changes in the temperature distribution at the bottom of the refrigerator envelope and the resulting dynamic effects, and a decrease in energy consumption of the entire system. Consequently, there are lower CO2 emissions to the environment, making household refrigerators more efficient and sustainable.